National Geographic Tales of the Weird : Unbelievable True Stories - Edited by Braun, David (Washington, D.C. National Geographic Society, 2012)
Documents abnormalities and facts on topics ranging from the human body and prehistoric life to unusual insects and birds, profiling such phenomena as flying sharks, zombie ants, and the universe's darkest planet.
Unbelievable True Stories.
Keywords: Curiosities and wonders